A Reactive Molecular Dynamics Study of Atomistic Mechanisms During Synthesis of MoS2 Layers by Chemical Vapor Deposition. (15th January 2018) - Hong, Sungwook; Krishnamoorthy, Aravind; Sheng, Chunyang; Kalia, Rajiv K.; Nakano, Aiichiro; Vashishta, Priya
ABSTRACT: Transition metal dichalcogenide (TMDC) monolayers like MoS2 are promising materials for future electronic applications. Large-area monolayer MoS2 samples for these applications are typically synthesized by chemical vapor deposition (CVD) using MoO3 reactants and gas-phase sulfur precursors. Recent experimental studies have greatly improved our understanding of reaction pathways in the CVD growth process. However, atomic mechanisms of sulfidation process remain to be fully elucidated. In this work, we present quantum-mechanically informed and validated reactive molecular dynamics (RMD) simulations for CVD synthesis of MoS2 layers using S2 precursors. Our RMD simulations clarify atomic-level reaction pathways for the sulfidation of MoO3 surfaces by S2, which is a critical reaction step for CVD synthesis of MoS2 layers. These results provide a better understanding of the sulfidation process for the scalable synthesis of defect-free MoS2 and other TMDC materials.